(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This scientific article explores strategies aimed at ensuring qualifications are attuned to the dynamic needs of the labor market while maintaining flexibility across sectors, as well as regional and national boundaries. Focusing on the development of pertinent qualifications within priority sectors, the article delves into the collaborative efforts geared towards expanding career opportunities and fostering adaptability within the labor market.